Effect of cumulative fertilizer dressings on the phosphorus status of mineral soils I Changes in inorganic phosphorus fractions - Hartikainen, Helinä (Agricultural and Food Science, 1989)
Surface soil samples were collected from 16 P fertilization trials before onset of the experiments and after seven years of cultivation. The changes in the inorganic P fractions were investigated in plots amended annually with 0, 30 or 60 kg of P ha-1. In the clay soils, cultivation without P fertilization depleted the NH4F-extractable and NaOH-extractable P reserves by 22—69 kg ha-1 ; in the coarser soils, the respective depletion was 8—140 kg ha-1. H2S04-soluble P decreased in seven soils by 16—34 kg ha-1. In the plots amended totally with 210 or 420 kg of P ha-1, on the other hand, these P fractions increased by 24—174 and 46—368 kg ha-1, respectively. The higher the P dressing was, the more the added P tended to accumulate in the fluoride-soluble form as compared to the alkali-soluble form.